RAINFALL INTERPOLATION ANALYSIS ON RIVER KADUNA CATCHMENT FOR CLIMATE CHANGE ASSESSMENT (Nigerian Journal of Technology, 2018)
The Inverse Distance Weighing (IDW) technique for rainfall interpolation considered by researchers as a suitable method for predicting missing rainfall records was used to estimate missing rainfall records in River Kaduna Catchment area from 1979-1990. Distances among respective rainfall stations were used to calculate the weighing factor for stations with missing records and radius of influence of 22.5-201km. The Root Mean Square Error (RMSE) was used to test the accuracy of the assessment and the results were validated using correlation coefficient. From the results of the analysis through optimization of steps of ? values and radius of influence, the smaller the optimum parameter value the better the prediction and in most cases the accuracy increases at  short optimum search radii, also small amount and long duration rainfall values enhances the prediction potential of the IDW. http://dx.doi.org/10.4314/njt.v37i3.33